Studies of the dependence of pollutant emissions on the operational parameters of the GHB, stationary and ship-type GPU’s - Terehov Aleksandr; Huaman de los Eros Federico; Bespalov Ilya; Galimov Aydar; Mavlyutova Svetlana (E3S Web of Conferences)
The article analyzes the influence of the operational parameters of stationary and ship-type gas pumping units (GPA) on the emission of pollutants (ZA). The most significant thermogasodynamic parameters have been determined for the development of mathematical models of NOx and CO emissions, on the basis of which a subsystem for environmental monitoring of pollutant emissions as part of the Digital Compressor Station system will be designed. The distinctive features of gas heating units from classic gas heaters and the features of their operation affecting the emissions of pollutants are also presented. The results of experimental measurements of NOx and CO emissions for gas heating units are presented.